2016
DOI: 10.5070/d3221029792
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal extramammary Paget’s disease-associated adenocarcinoma: a rare condition of flexoral skin of multiple sites

Abstract: Case presentationMultifocal extramammary Paget's disease-associated adenocarcinoma: a rare condition of flexoral skin of multiple sites Dermatology Online Journal 22 (1): 9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The other indicators are very similar, such as: the onset age is middle-aged and elderly people; All skin lesions are unilateral armpits; There are only a small number of concurrent local tumors. Wolf et al [ 8 ] believe that EMPD can present various clinical manifestations, so it is often misdiagnosed initially. Therefore, when recurrent erosive erythema occurs in the armpit area and the treatment effect is not satisfactory, it is recommended to undergo biopsy and immunopathological chemical examination early to rule it out.…”
Section: Discussionmentioning
confidence: 99%
“…The other indicators are very similar, such as: the onset age is middle-aged and elderly people; All skin lesions are unilateral armpits; There are only a small number of concurrent local tumors. Wolf et al [ 8 ] believe that EMPD can present various clinical manifestations, so it is often misdiagnosed initially. Therefore, when recurrent erosive erythema occurs in the armpit area and the treatment effect is not satisfactory, it is recommended to undergo biopsy and immunopathological chemical examination early to rule it out.…”
Section: Discussionmentioning
confidence: 99%
“…We searched the English and Chinese literature and summarised our cases and other 18 multiple EMPD cases previously reported (Table 1). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The mean age at diagnosis was 74 years. Of the 20 identified cases of multiple location EMPD, 19 were men, 17 (85%) of these men were Asian, and only 3 were caucasian, including the only female.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, our review of the literature identified 9 additional cases with only 1 case report of triple EMPD from Belgium and 1 from the United States, although the latter did not specify race and ethnicity. [2][3][4][5][6][7][8] EMPD is characteristically slow growing, and clinical features include pink or white scaly ulcerated plaques often described as ''strawberries and cream.'' 9 The pathogenesis of primary EMPD is not well understood but has been thought to arise from pluripotent intraepithelial or adnexal cells.…”
Section: Discussionmentioning
confidence: 99%